A STUDY ON FOUR ANTIOXIDATION EFFECTS OF LYCIUM BARBARUM POLYSACCHARIDES IN VITRO - Zhang, Lili; Yanjun, Chen; Gu, jinxia; Zhang, Lan (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of the study was to investigate the in vitro antioxidation activity of lycium barbarum polysaccharides (LBP). Ultraviolet spectrophotometry was adopted to determine the capability of LBP to clear superoxide anions, hydroxyl radicals, DPPH free radicals and ABTS free radicals. The result showed that the law for LBP to clear superoxide anions, hydroxyl radicals and DPPH free radicals was that the clearance rate increased gradually with the increase of the concentration, and when the concentration reached a certain value, the clearance rate leveled off, while the IC50 for clearing ABTS free radicals was 47.158±6.231μg/ml. The study concluded that LBP is a good in vitro antioxidant.